Structured programs for the self-management of substance addiction consequences in outpatient services: A scoping review - Seabra, Paulo (2023)
Structured intervention programs are an important resource for supporting people with substance addiction. Although evidence suggests that they improve health outcomes, such as specifc symptoms, less is known about their impact on patients’ ability to self-manage the consequences of substance addiction. The aim of this review is to scope outpatient intervention programs focused on the self-management of substance addiction consequences. Approach. This review followed the Joanna Briggs Institute (JBI) methodology for scoping reviews. MEDLINE and CINAHL (through Ebsco), Psychology & Behavioral Sciences Collection (including PsycINFO) and Web of Science were screened to identify articles published in the last 10 years. Only primary research was included. Out of 891 records, 19 were eligible for this review—12 randomized controlled trials (RCT), 6 quasi-experimental study and 1 observational study. Those studies reported group interventions (10), individual interventions (8) and 1 mixed approach. The most common interventions were based on motivational strategies, relapse prevention and defnition of active plans for risky situations. 10 studies reported positive efects. The identifcation of structured programs may support the development of new approaches focused on empowerment and quality of life of people with substance addiction. Programs to empower patients for self-management of substance addiction consequences are often complex and rely on health professionals’ commitment. Nevertheless, they are a feasible approach that seems to beneft patients managing chronic conditions associated with substance addiction.